Modified argon laser therapy for benign tumor of the eyelid - Han, Jisang; Lee, Shin-Hyo; Choi, Chul Young; Khoramnia, Ramin; Kim, Jaemin; Shin, Hyun Jin (BMC ophthalmology, 2022)
To report about the therapy of benign eyelid tumors with a modified argon laser technique as an alternative to surgery.
Gesehen am 25.10.2022